Problematika Sistem Pendidikan Indonesia dan Solusinya - Sukari, Sukari; Winarno, Andhika Sarfatra (TSAQOFAH, 2025)
The world of education in Indonesia is still riddled with various problems. These problems lie in the input, process or output of educational institutions. This must be addressed immediately and solutions must be sought to create a more qualified national education. These problems can only be solved with the participation of all parties involved in the education system, such as parents, teachers, principals, the community, and also the students themselves. This study uses a descriptive qualitative method with a case study approach. Data were collected through literature studies and document analysis. Problems in the education system can occur in the input, process or output of an educational institution. The following are some problems that often occur in educational institutions based on the division of educational flows in an institution: a) Problems in input: lack of synergy between parents and institutions, b) Problems in the process: changes in the curriculum that burden teachers with administration and lack of time to educate, c) Problems in output: there are school alumni who have not been able to compete in the world of work or education. In the input of the education system, parents must be involved in educating their children as future leaders. In the process, namely within the scope of the school, a culture of organization, socialization and good character must be held. Teachers must actively educate and should prioritize character education rather than just delivering material or filling administrative duties. At the output of the education system, alumni or graduates must be active, creative, and persistent at the next level or in the world of work. People who think creatively tend to be more able to survive in unpleasant conditions and situations.